RASIO TENAGA PENDIDIK, RASIO TENAGA KESEHATAN, DAN CAPAIAN PEMBANGUNAN MANUSIA DI INDONESIA DALAM ANALISIS SPASIAL - Opan Fauzan Hamdan (Syiah Kuala University, 2019)
AbstractThe achievement of the Human Development Index (HDI) in Indonesia when compared to other countries is still unsatisfactory. Base on UN data, Indonesia is ranked 116th out of 189 countries. The disparity in HDI achievement between regions is also still high. There is a pattern of grouping in the achievement of HDI, where regions with with high HDI are more concentrated in western part of Indonesia. This research was conducted to study how the relationship between the ratio of educators and ratio of health workers to the achievement of HDI with spatial analysis. The control variables used in analyzing these relationships include economic, social, and demographic variables. This study uses secondary data derived from publication of Indeks Pembangunan Manusia, Daerah Dalam Angka , Indikator Kesejahteraan Rakyat and SUSENAS data in 2017 that has been processed by BPS. The unit of analysis in this study is all regency/city in Indonesia. By using a spatial lag regression model, the results of this study show that there is a significant spatial relationship between regency/cities in Indonesia where when is an increase of HDI in a regency/city it will have a positive effect on the regency/city in the surrounding. The ratio of educators at the elementary level and the ratio of health workers to both doctors or non-doctors has a positive and significant effect on HDI achievement. The comparison between spatial regression model and ordinary least square (OLS) model shows that the spatial model is better used to analyze HDI.